SOME APPLICATIONS OF THE NUCLEAR MAGNETIC RESONANCE (NMR) IN THE MEDICINE - DANG , VAN CANH; NGUYEN , TRUONG LUYEN; MAI , HUU THUAN; NGUYEN , TRONG LUU (Nuclear Science and Technology, 2011)
The authors report the modern applications of nuclear magnetic resonance (NMR) to the medicine. That is the nuclear magnetic resonance imaging (MRI), the magnetic resonance spectroscopy in-vivo (MRS), functional nuclear magnetic resonance (fNMR), diffusion tensor_MRI (dt_MRI), and their close relationship. These methods are exact, powerful tools for the detection and characterization of the diseases on the basis of the physical, biochemical properties of the systems.